Development of Urban Tourism along the Seaside Resort Town of Limbe in Cameroon - MAYI, Amélie-Emmanuelle MAYI; BAMBOYE, Gilbert FONDZE; NDOUMBE, Terence NCHA (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023, 2023)
The city of Limbe is endowed with tourism potential whose development has several advantages to the development of the economy of the area. Tourism has become one of the vibrant sectors in the development of economies in both developed and developing countries of the world. The contribution of tourism to economic development lies first with the identification of potentials and the various stakeholders involved in their development. The purpose of this study is to identify and locate key tourist attractions in Limbe, identify the actors involved in tourism development and the role they play, to investigate the implications of urban-tourism, in the tourism sector of Limbe. Purposive and random sampling techniques were used to collect data from the field in the study. Questionnaires and interview were used as instruments to obtain data from 333 residents drawn from the three council areas that make up the Limbe metropolitan area. Data collected were analysed by using simple statistical methods by tabulation and categorisation. Treated data is presented in forms of tables, graphs, photographs, and figure. The findings reveal amongst others that the tourism potentials of Limbe and its surroundings are enormous and attract many tourists into Limbe. It is also realised that tourism development in Limbe is influenced by both public and private actors. More so, urban regeneration and events such as Limbe FESTAC and AFCON are strategies used to promote urban-tourism in Limbe. Urban-tourism in Limbe has socio-cultural, spatial and economic implications. By implication, the participation of different actors is very necessary for tourism development in the city. The results are significant in crafting the future of urban-tourism projects and practices.